2022
DOI: 10.3389/fcimb.2022.1035364
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics and genomic analysis of a novel Vibrio parahaemolyticus phage phiTY18 isolated from the coastal water of Xiamen China

Abstract: Vibrio parahaemolyticus is a common pathogen usually controlled by antibiotics in mariculture. Notably, traditional antibiotic therapy is becoming less effective because of the emergence of bacterial resistance, hence new strategies need to be found to overcome this challenge. Bacteriophages, a class of viruses that lyse bacteria, can help us control drug-resistant bacteria. In this study, a novel Vibrio parahaemolyticus phage phiTY18 isolated from the coastal water of Xiamen was explored. Transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Similar to our results, Foschino et al reported the optimal MOI for L. sanfranciscensis phage EV3, which was isolated from sourdough, was 0.01 [26]. Liu et al found that the optimal MOI of phage phiTY18 was 0.01 [27]. The optimal MOI for L. brevis phage was 10 [28].…”
Section: Determination Of Optimal Multiplicity Of Infection (Moi)supporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our results, Foschino et al reported the optimal MOI for L. sanfranciscensis phage EV3, which was isolated from sourdough, was 0.01 [26]. Liu et al found that the optimal MOI of phage phiTY18 was 0.01 [27]. The optimal MOI for L. brevis phage was 10 [28].…”
Section: Determination Of Optimal Multiplicity Of Infection (Moi)supporting
confidence: 90%
“…At the same time, Figure 1 showed that with the increase in MOI, the titer of the LFP02 phage had two peaks, yet the maximum titer was only one. A similar situation also appeared in the studies by Liu et al [27] and Mercanti et al [29]. As for the reasons for the decline, Mercanti et al suggested that this may be due to the limited number of attachment sites available to phages on the cell wall, or another type of spatial obstruction [29].…”
Section: Determination Of Optimal Multiplicity Of Infection (Moi)supporting
confidence: 58%
“…Vibrio parahaemolyticus , which is a prevalent pathogenic bacterium, poses a threat to both marine organisms and humans, thus resulting in illnesses. V. parahaemolyticus phages such as F23s2, H256D1, and the recently discovered phage phiTY18 showed inhibitory effects, thus offering alternatives to antibiotics to control V. parahaemolyticus [65] , [66] . However, certain viruses, such as the white spot syndrome virus, the Singapore grouper iridovirus, and the infectious subcutaneous and hematopoietic necrosis viruses in aquaculture, exhibit a high fatality rate, thus posing a severe threat to crustaceans and groupers and hindering economic development [67] [69] .…”
Section: Effects Of Marine Aquaculture On Fungal and Viral Communitiesmentioning
confidence: 99%
“…In contrast, Vibrio mimicus ( Li et al., 2020 ) and Vibrio cholerae ( Silva and Benitez, 2016 ) are most common in freshwater. Among them, V. parahaemolyticus , a Gram-negative bacterium, is found in various marine and freshwater products, including shrimp, crabs, and oysters ( Mahmoud, 2014 ; Liu et al., 2022 ). More gravely, it is the prominent cause of seafood-related contagions and mortality globally, encompassing three categories of diseases: septicemia, infections in wound, and gastroenteritis ( Kim et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%